NEW YAM FESTIVALS IN IGBOLAND - Onwurah, Emeka (Journal of Dharma, 1990)
Yam,' the principal-cash crop of the Igbo of Nigeria was the mainstay of the people's economy until recent times. However, it still remains the main occupation of the backwood communities. Hence the dominating importance of yam festivals both in the past and in contemporary times.